Trends in lifetime risk and years of life lost due to diabetes in the USA, 1985-2011: a modelling study - Gregg, Edward W; Zhuo, Xiaohui; Cheng, Yiling J; Albright, Ann L; Narayan, K M Venkat; Thompson, Theodore J (The lancet. Diabetes & endocrinology, 2014)
Diabetes incidence has increased and mortality has decreased greatly in the USA, potentially leading to substantial changes in the lifetime risk of diabetes. We aimed to provide updated estimates for the lifetime risk of development of diabetes and to assess the effect of changes in incidence and mortality on lifetime risk and life-years lost to diabetes in the USA. We incorporated data about diabetes incidence from the National Health Interview Survey, and linked data about mortality from 1985 to 2011 for 598 216 adults, into a Markov chain model to estimate remaining lifetime diabetes risk, years spent with and without diagnosed diabetes, and life-years lost due to diabetes in three cohorts: 1985-89, 1990-99, and 2000-11. Diabetes was determined by self-report and was classified as any diabetes, excluding gestational diabetes. We used logistic regression to estimate the incidence of diabetes and Poisson regression to estimate mortality. On the basis of 2000-11 data, lifetime risk of diagnosed diabetes from age 20 years was 40·2% (95% CI 39·2-41·3) for men and 39·6% (38·6-40·5) for women, representing increases of 20 percentage points and 13 percentage points, respectively, since 1985-89. The highest lifetime risks were in Hispanic men and women, and non-Hispanic black women, for whom lifetime risk now exceeds 50%. The number of life-years lost to diabetes when diagnosed at age 40 years decreased from 7·7 years (95% CI 6·5-9·0) in 1990-99 to 5·8 years (4·6-7·1) in 2000-11 in men, and from 8·7 years (8·4-8·9) to 6·8 years (6·7-7·0) in women over the same period. Because of the increasing diabetes prevalence, the average number of years lost due to diabetes for the population as a whole increased by 46% in men and 44% in women. Years spent with diabetes increased by 156% in men and 70% in women. Continued increases in the incidence of diagnosed diabetes combined with declining mortality have led to an acceleration of lifetime risk and more years spent with diabetes, but fewer years lost to the disease for the average individual with diabetes. These findings mean that there will be a continued need for health services and extensive costs to manage the disease, and emphasise the need for effective interventions to reduce incidence. None.